Rencana Bisnis Peternakan Ayam Ras Petelur Pt. Sinar Farm Di Provinsi Maluku - Prasetyo Prasetyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The level of consumption for eggs in Maluku can not be fulfilled by local production, therefore there is a need of supply from other regions such as Makassar and Surabaya. This situation opens for dependence on the supply of eggs from other regions is very high, which indicates that there is an opportunity for business and large market share for this business in Maluku. Seeing the opportunities that exist, the idea to open a layer farming in Maluku is feasible to be implemented. The marketing targets of the products are retail merchants in the market, grocery stores and collective merchant between regions. In this business plan, there are income statement and cash flow statement of the company for the next 5 years. Based on calculations that have been done, the results of the Net Present Value (NPV) is positive, and payback period is faster than the time specified. Thus, it can be concluded that investment in layer farming is feasible and profitable.